Die Deutschdidaktik in Polen muss umkehren. Eine RetroPerspektive. German language education in Poland must change. A retro-perspective view. - Lewicka, Grażyna (Glottodidactica, 2016)
The article deals with the situation of German language education in Poland from a retro-perspective viewpoint which consists in revisiting the past 50 years, from the moment the first issue of Glottodidactica appeared, and modifying it from the present by giving suggestions which could cause positive changes in the Polish tradition of language teaching and learning methodology.